A Model-Based Testing Framework for Automotive Embedded Systems - Marinescu, Raluca; Saadatmand, Mehrdad; Bucaioni, Alessio; Seceleanu, Cristina; Pettersson, Paul (EUROMICRO (IEEE Computer Society Press), 2014)
Architectural models, such as those described in the east language, represent convenient abstractions to reason about automotive embedded software systems. To enjoy the fully-fledged advantages of reasoning, EAST-ADL models could benefit from a component-aware analysis framework that provides, ideally, both verification and model-based test-case generation capabilities. While different verification techniques have been developed for architectural models, only a few target EAST-ADL. In this paper, we present a methodology for code validation, starting from EAST-ADL artifacts. The methodology relies on: (i) automated model-based test-case generation for functional requirements criteria based on the EAST-ADL model extended with timed automata semantics, and (ii) validation of system implementation by generating Python test scripts based on the abstract test-cases. The scripts represent concrete test-cases that are executable on the system implementation. We apply our methodology to analyze the ABS function implementation of the Brake-by-Wire system prototype.